5.3.3 Problems 201 to 300

Table 5.289: Second order ode

#

ODE

Mathematica

Maple

810

\[ {}y^{\prime \prime }+25 y = 0 \]

811

\[ {}y^{\prime \prime }-3 y^{\prime }+2 y = 0 \]

812

\[ {}y^{\prime \prime }+y^{\prime }-6 y = 0 \]

813

\[ {}y^{\prime \prime }+y^{\prime } = 0 \]

814

\[ {}y^{\prime \prime }-3 y^{\prime } = 0 \]

815

\[ {}y^{\prime \prime }+2 y^{\prime }+y = 0 \]

816

\[ {}y^{\prime \prime }-10 y^{\prime }+25 y = 0 \]

817

\[ {}y^{\prime \prime }-2 y^{\prime }+2 y = 0 \]

818

\[ {}y^{\prime \prime }+6 y^{\prime }+13 y = 0 \]

819

\[ {}x^{2} y^{\prime \prime }-2 x y^{\prime }+2 y = 0 \]

820

\[ {}x^{2} y^{\prime \prime }+2 x y^{\prime }-6 y = 0 \]

821

\[ {}x^{2} y^{\prime \prime }-x y^{\prime }+y = 0 \]

822

\[ {}x^{2} y^{\prime \prime }+x y^{\prime }+y = 0 \]

823

\[ {}y^{\prime \prime }-3 y^{\prime }+2 y = 0 \]

824

\[ {}y^{\prime \prime }+2 y^{\prime }-15 y = 0 \]

825

\[ {}y^{\prime \prime }+5 y^{\prime } = 0 \]

826

\[ {}2 y^{\prime \prime }+3 y^{\prime } = 0 \]

827

\[ {}2 y^{\prime \prime }-y^{\prime }-y = 0 \]

828

\[ {}4 y^{\prime \prime }+8 y^{\prime }+3 y = 0 \]

829

\[ {}4 y^{\prime \prime }+4 y^{\prime }+y = 0 \]

830

\[ {}9 y^{\prime \prime }-12 y^{\prime }+4 y = 0 \]

831

\[ {}6 y^{\prime \prime }-7 y^{\prime }-20 y = 0 \]

832

\[ {}35 y^{\prime \prime }-y^{\prime }-12 y = 0 \]

833

\[ {}x^{2} y^{\prime \prime }+x y^{\prime }-y = 0 \]

834

\[ {}x^{2} y^{\prime \prime }+2 x y^{\prime }-12 y = 0 \]

835

\[ {}4 x^{2} y^{\prime \prime }+8 x y^{\prime }-3 y = 0 \]

836

\[ {}x^{2} y^{\prime \prime }+x y^{\prime } = 0 \]

837

\[ {}x^{2} y^{\prime \prime }-3 x y^{\prime }+4 y = 0 \]

838

\[ {}y^{\prime \prime }+y = 3 x \]

839

\[ {}y^{\prime \prime }-4 y = 12 \]

840

\[ {}y^{\prime \prime }-2 y^{\prime }-3 y = 6 \]

841

\[ {}y^{\prime \prime }-2 y^{\prime }+2 y = 2 x \]

842

\[ {}y^{\prime \prime }+2 y = 4 \]

843

\[ {}y^{\prime \prime }+2 y = 6 x \]

844

\[ {}y^{\prime \prime }+2 y = 6 x +4 \]

845

\[ {}y^{\prime \prime }-4 y = 0 \]

846

\[ {}2 y^{\prime \prime }-3 y^{\prime } = 0 \]

847

\[ {}y^{\prime \prime }+3 y^{\prime }-10 y = 0 \]

848

\[ {}2 y^{\prime \prime }-7 y^{\prime }+3 y = 0 \]

849

\[ {}y^{\prime \prime }+6 y^{\prime }+9 y = 0 \]

850

\[ {}y^{\prime \prime }+5 y^{\prime }+5 y = 0 \]

851

\[ {}4 y^{\prime \prime }-12 y^{\prime }+9 y = 0 \]

852

\[ {}y^{\prime \prime }-6 y^{\prime }+13 y = 0 \]

853

\[ {}y^{\prime \prime }+8 y^{\prime }+25 y = 0 \]

854

\[ {}y^{\prime \prime }-4 y^{\prime }+3 y = 0 \]

855

\[ {}9 y^{\prime \prime }+6 y^{\prime }+4 y = 0 \]

856

\[ {}y^{\prime \prime }-6 y^{\prime }+25 y = 0 \]

857

\[ {}y^{\prime \prime }-2 i y^{\prime }+3 y = 0 \]

858

\[ {}y^{\prime \prime }-i y^{\prime }+6 y = 0 \]

859

\[ {}y^{\prime \prime } = \left (-2+2 i \sqrt {3}\right ) y \]

860

\[ {}x^{2} y^{\prime \prime }+x y^{\prime }+9 y = 0 \]

861

\[ {}x^{2} y^{\prime \prime }+7 x y^{\prime }+25 y = 0 \]

862

\[ {}\frac {x^{\prime \prime }}{2}+3 x^{\prime }+4 x = 0 \]

863

\[ {}3 x^{\prime \prime }+30 x^{\prime }+63 x = 0 \]

864

\[ {}x^{\prime \prime }+8 x^{\prime }+16 x = 0 \]

865

\[ {}2 x^{\prime \prime }+12 x^{\prime }+50 x = 0 \]

866

\[ {}4 x^{\prime \prime }+20 x^{\prime }+169 x = 0 \]

867

\[ {}2 x^{\prime \prime }+16 x^{\prime }+40 x = 0 \]

868

\[ {}x^{\prime \prime }+10 x^{\prime }+125 x = 0 \]

869

\[ {}y^{\prime \prime }+16 y = {\mathrm e}^{3 x} \]

870

\[ {}y^{\prime \prime }-y^{\prime }-2 y = 3 x +4 \]

871

\[ {}y^{\prime \prime }-y^{\prime }-6 y = 2 \sin \left (3 x \right ) \]

872

\[ {}4 y^{\prime \prime }+4 y^{\prime }+y = 3 x \,{\mathrm e}^{x} \]

873

\[ {}y^{\prime \prime }+y^{\prime }+y = \sin \left (x \right )^{2} \]

874

\[ {}2 y^{\prime \prime }+4 y^{\prime }+7 y = x^{2} \]

875

\[ {}y^{\prime \prime }-4 y = \sinh \left (x \right ) \]

876

\[ {}y^{\prime \prime }-4 y = \cosh \left (2 x \right ) \]

877

\[ {}y^{\prime \prime }+2 y^{\prime }-3 y = 1+x \,{\mathrm e}^{x} \]

878

\[ {}y^{\prime \prime }+9 y = 2 \cos \left (3 x \right )+3 \sin \left (3 x \right ) \]

879

\[ {}y^{\prime \prime }+9 y = 2 x^{2} {\mathrm e}^{3 x}+5 \]

880

\[ {}y^{\prime \prime }-2 y^{\prime }+2 y = {\mathrm e}^{x} \sin \left (x \right ) \]

881

\[ {}y^{\prime \prime }+4 y = 3 x \cos \left (2 x \right ) \]

882

\[ {}y^{\prime \prime }+3 y^{\prime }+2 y = x \left ({\mathrm e}^{-x}-{\mathrm e}^{-2 x}\right ) \]

883

\[ {}y^{\prime \prime }-6 y^{\prime }+13 y = x \,{\mathrm e}^{3 x} \sin \left (2 x \right ) \]

884

\[ {}y^{\prime \prime }+4 y = 2 x \]

885

\[ {}y^{\prime \prime }+3 y^{\prime }+2 y = {\mathrm e}^{x} \]

886

\[ {}y^{\prime \prime }+9 y = \sin \left (2 x \right ) \]

887

\[ {}y^{\prime \prime }+y = \cos \left (x \right ) \]

888

\[ {}y^{\prime \prime }-2 y^{\prime }+2 y = 1+x \]

889

\[ {}y^{\prime \prime }+y^{\prime }+y = \sin \left (x \right ) \sin \left (3 x \right ) \]

890

\[ {}y^{\prime \prime }+9 y = \sin \left (x \right )^{4} \]

891

\[ {}y^{\prime \prime }+y = x \cos \left (x \right )^{3} \]

892

\[ {}y^{\prime \prime }+3 y^{\prime }+2 y = 4 \,{\mathrm e}^{x} \]

893

\[ {}y^{\prime \prime }-2 y^{\prime }-8 y = 3 \,{\mathrm e}^{-2 x} \]

894

\[ {}y^{\prime \prime }-4 y^{\prime }+4 y = 2 \,{\mathrm e}^{2 x} \]

895

\[ {}y^{\prime \prime }-4 y = \sinh \left (2 x \right ) \]

896

\[ {}y^{\prime \prime }+4 y = \cos \left (3 x \right ) \]

897

\[ {}y^{\prime \prime }+9 y = \sin \left (3 x \right ) \]

898

\[ {}y^{\prime \prime }+9 y = 2 \sec \left (3 x \right ) \]

899

\[ {}y^{\prime \prime }+y = \csc \left (x \right )^{2} \]

900

\[ {}y^{\prime \prime }+4 y = \sin \left (x \right )^{2} \]

901

\[ {}y^{\prime \prime }-4 y = x \,{\mathrm e}^{x} \]

902

\[ {}x^{2} y^{\prime \prime }+x y^{\prime }-y = 72 x^{5} \]

903

\[ {}x^{2} y^{\prime \prime }-4 x y^{\prime }+6 y = x^{3} \]

904

\[ {}x^{2} y^{\prime \prime }-3 x y^{\prime }+4 y = x^{4} \]

905

\[ {}4 x^{2} y^{\prime \prime }-4 x y^{\prime }+3 y = 8 x^{{4}/{3}} \]

906

\[ {}x^{2} y^{\prime \prime }+x y^{\prime }+y = \ln \left (x \right ) \]

907

\[ {}\left (x^{2}-1\right ) y^{\prime \prime }-2 x y^{\prime }+2 y = x^{2}-1 \]

908

\[ {}x^{\prime \prime }+9 x = 10 \cos \left (2 t \right ) \]

909

\[ {}x^{\prime \prime }+4 x = 5 \sin \left (3 t \right ) \]